(untitled) (Research, Society and Development, 2024)
Artivism, as a form of activism that combines art and social engagement, has played a significant role in addressing social, cultural and political issues in the Beach of Redinha-RN Tourist Complex. Therefore, the objective of this research was to analyze the artistic and socio-environmental impacts, which go through a process of historical-cultural erasure on Redinha beach-RN, with the construction of the Tourist Complex on the bank of the Potengi River. As a result, the artivist work of the performance “What does the mouth of the river say?” was developed; with collection of material from the Potengi River and the composition of the assemblage “Oferendo-te” and the second part with the assembly of costumes, scenography and choreography recorded in the photo essay “Recebo-te”. In conclusion, artivism represents a dynamic and multifaceted form of activism that harnesses the power of art to address social, cultural, and political issues.